2020
DOI: 10.1002/admi.202000305
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Fabrication of Universal Slippery Lubricated Surfaces

Abstract: lubricant on the LIS is a fluid, substrates for the LIS should possess a porous or textured structure to induce the capillary force that retains the lubricant layer. In addition, the substrate must have a hydrophobic surface with a low surface energy to achieve a stable lubricant layer; the low surface energy is crucial since the total interfacial energy among substrate, liquid drop, and lubricant should be lower than that between substrate and liquid drop for effective repulsion of the liquid drops. [14,15] I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
1
24
2
Order By: Relevance
“…A second approach to create LISs are polymer brushes that are bound to a solid surface. [ 21,22,29–34 ] Typically, alkylsiloxanes such as polydimethylsiloxane (PDMS) brushes are used to provide a liquid‐like, low surface energy surface. The liquid‐like molecule chains can be coupled via silane chemistry, [ 32 ] via π‐electron interactions after surface silanization, [ 33 ] from acidic sol–gel chemistry [ 21,29 ] or by partial thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach to create LISs are polymer brushes that are bound to a solid surface. [ 21,22,29–34 ] Typically, alkylsiloxanes such as polydimethylsiloxane (PDMS) brushes are used to provide a liquid‐like, low surface energy surface. The liquid‐like molecule chains can be coupled via silane chemistry, [ 32 ] via π‐electron interactions after surface silanization, [ 33 ] from acidic sol–gel chemistry [ 21,29 ] or by partial thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…The C 1s peak is composed of CF 3 (293.8 eV), CF 2 (292.4 eV), C-O/C-OH (286.5 eV), and C-C/C-H/C-Si (284.8 eV) peaks ( Figure 1 I). The Si 2p peak is composed of Si-C (102.0 eV), Si-O (103.3 eV) and Si- O -Si (103.9 eV) peaks ( Figure S4 ) ( Chen et al., 2020 ; Qing et al., 2020 ). The F content reaches 37.84 at%, indicating presence of abundant perfluorodecyl groups on the surface of the fabric ( Li et al., 2019a ).…”
Section: Resultsmentioning
confidence: 99%
“…The surface of nano/microparticles can be modified by attaching various organics with linking groups. The linking group of the organic forms a bond with the surface, whereas the other part of the molecule defines the surface property. Polysiloxanes (PSOs), which are polymers based on siloxane backbones, are promising materials for modifying the particle surfaces. Due to the stable siloxane bond with relatively high bonding energy (444 kJ mol –1 ), the PSOs exhibit good chemical and thermal stabilities and biocompatibility. In addition, the PSOs can be decomposed by hydrolysis in soil, allowing more eco-friendly and sustainable chemistry . Recently, it was shown that the hydrosilylation reaction can be used to graft PSOs onto the surface of oxides. The siloxane backbone is cleaved in the presence of hydroxyl groups and subsequently grafted to the hydroxyl groups on the surface of oxides, forming a PSO brush of a few nanometers in thickness. The PSO brush grafting reaction has also been applied to modify the surfaces of metal oxides having surface hydroxyl groups, resulting in the formation of various functional surfaces, such as hydrophobic photocatalysts, , stable lubricant impregnated surfaces, ,, and a blood repelling dress .…”
Section: Introductionmentioning
confidence: 99%